INFLUENCE OF ENALAPRIL, DIGOXIN, ATENOLOL AND DILTIAZEM ON LIPID PEROXIDATION IN EXPERIMENTAL MODEL OF COMPLEX METABOLIC DISORDERS - A. A. Usanova; A. A. Aleksandrovsky; A. V. Zorkina; O. M. Kiselеv (Столичная издательская компания, 2016)
Aim. To study influence of enalapril, digoxin, atenolol and diltiazem on lipid peroxidation and antioxidative protection in experimental disorders of glucose and lipid metabolism.Material and methods. White nonlinear mice were used for modeling of the complex metabolic disorders by alloxan and cholesterol infusion. Evaluation of acute drug toxicity and indicators of lipid peroxidation and antioxidant protection was performed. Superoxide dismutase and catalase activity, malondialdehyde concentration were evaluated.Results. Toxicity of digoxin, diltiazem, atenolol in complex metabolic disorders was increased, and toxicity of enalapril was unchanged. Enalapril had antioxidant effect. Atenolol had prooxidative effect in myocardium and kidneys, and diltiazem - in kidneys.Conclusion. Enalapril showed antioxidant effect and decreased concentration of secondary products of lipid peroxidation in renal tissue. It may be considered as the first line drug in complex metabolic disorders.